The Routledge international handbook of learning with technology in early childhood - Kucirkova, Natalia; Rowsell, Jennifer 1969-; Falloon, Garry (Routledge international handbooks of education, 2019)
"This book brings together innovative work happening in childhood research across disciplinary boundaries and across the world. It focuses specifically on the most cutting-edge, innovative methodological approaches in the study of children's use and learning with digital technologies and children's experiences of key 21st century trends (e.g. immigration or multiculturalism). A true effort is made to have dialogues across diverse fields and contested fields of research (including educational psychology, post-humanist literacy, narrative approaches, developmental approaches). The volume is a substantive and strategic collection of international approaches to early childhood and technologies"--